Head and Neck Myxoma Presenting as Isolated Laryngeal Polyp - Smriti Panda; Rajeev Kumar; Vikram Raj Gopinath; Prem Sagar (Case Reports in Otolaryngology)
Myxoma is a benign tumour with a propensity for local infiltration and recurrence. Laryngeal myxoma presents as a submucosal polyp. Being an uncommon tumour and mimicking vocal cord polyp, only anecdotal evidence is available in the literature. The literature was reviewed from 1986 onwards using the keywords “myxoma” and “larynx.” The databases used were PubMed, Google Scholar, Scopus, and Web of Science. Along with this, we also report our case of vocal fold myxoma. We found a total of 19 studies reporting laryngeal myxoma. Laryngeal myxoma typically affects males in the 6th decade with a history of smoking. Unlike myxomas originating outside the larynx, recurrence is not widely described, and microlaryngeal surgery will usually suffice. Laryngeal myxomas should definitely be kept in the list of differential diagnosis when dealing with a benign-looking vocal fold lesion.